TYPOLOGIES OF CHARACTER IN LITERARY STUDIES: THEORY AND PRACTICE (SCIENCE TIME JOURNAL, 2026)
This article examines the typology of character in literary studies, focusing on its theoretical foundations and practical applications in narrative analysis. It clarifies the distinction between character and personality, outlines major approaches to characterization, and classifies key character types. Particular attention is given to dual character relationships as a central analytical framework. Drawing on examples from American and British literature, the study demonstrates how contrasting character pairings contribute to thematic development and narrative complexity. The findings highlight the importance of character typology in understanding literary texts and their broader cultural and psychological implications.